2007
DOI: 10.1038/ni1469
|View full text |Cite
|
Sign up to set email alerts
|

L-selectin-negative CCR7− effector and memory CD8+ T cells enter reactive lymph nodes and kill dendritic cells

Abstract: T lymphocytes lacking the lymph node-homing receptors L-selectin and CCR7 do not migrate to lymph nodes in the steady state. Instead, we found here that lymph nodes draining sites of mature dendritic cells or adjuvant inoculation recruited L-selectin-negative CCR7- effector and memory CD8+ T cells. This recruitment required CXCR3 expression on T cells and occurred through high endothelial venules in concert with lumenal expression of the CXCR3 ligand CXCL9. In reactive lymph nodes, recruited T cells establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
218
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(232 citation statements)
references
References 54 publications
13
218
1
Order By: Relevance
“…The stochastic nature of interaction between immune cells during immune responses can predict the generation of effector CD8 T cells with phenotypes similar to the one described in this manuscript (31,35). This will be especially true for the secondary response where rapidly reactivated Ag-specific memory CD8 T cells would quickly deplete Ag-carrying APCs, creating a condition permissive for brief stimulation of naive CD8 T cells (36). This scenario would allow naive CD8 T cells involved in an immune response to bypass full effector differentiation and transit directly into the memory stage (37), thus preventing excessive generation of full-blown effector CD8 T cells while preserving efficient recruitment into the memory pool.…”
Section: Discussionmentioning
confidence: 99%
“…The stochastic nature of interaction between immune cells during immune responses can predict the generation of effector CD8 T cells with phenotypes similar to the one described in this manuscript (31,35). This will be especially true for the secondary response where rapidly reactivated Ag-specific memory CD8 T cells would quickly deplete Ag-carrying APCs, creating a condition permissive for brief stimulation of naive CD8 T cells (36). This scenario would allow naive CD8 T cells involved in an immune response to bypass full effector differentiation and transit directly into the memory stage (37), thus preventing excessive generation of full-blown effector CD8 T cells while preserving efficient recruitment into the memory pool.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, memory cells might also use similar mechanisms to control boosting responses. Recently, it has been shown that effector and effector memory cells, which are normally excluded from resting lymph nodes, can enter reactive (inflamed) lymph nodes in a CXCR3-dependent manner and kill DCs (42). Additionally, memory CD8 ϩ T cells might clear Ag in the periphery, preventing it from being cross-presented in the lymphoid tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Gene and protein expression analysis showed that although these cells were located in the LNs, γδ Trm failed to express CD62L and CCR7, but expressed CD69, CXCR3, and CXCR6. The chemokine receptor CXCR3 has previously been implicated in mediating CCR7-independent homing of activated CD8 T cells to reactive LNs (26). Because γδ Trm cells did not express the typical LN homing receptors, the expression of CXCR3 likely allowed these cells to migrate to and remain in the LNs following infection.…”
Section: Discussionmentioning
confidence: 99%